Analisis Pengaruh Investasi, Tenaga Kerja Dan Pendapatan Per Kapita Terhadap Jumlah Penduduk Miskin Di Provinsi Jawa Timur - Syaharani Cahyani Pramesti; Asmara, Kiky; Laily Nisa, Fauzatul (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2025)
This study aims to analyze the effect of investment, labor, and per capita income on the number of poor people in East Java Province during the period 2019-2023. This study uses a quantitative approach with a panel data regression analysis method covering 38 districts/cities in East Java Province. The Fixed Effect Model was chosen as the best estimation model based on the Chow and Hausman Test. The results of the study indicate that the three independent variables simultaneously affect the number of poor people. Partially, increasing investment, labor and per capita income have a negative and significant effect on the number of poor people. This study indicates the importance of an economic development strategy that focuses on increasing investment, expanding employment opportunities and equalizing per capita income to reduce the number of poor people sustainably. This research is expected to be a reference for policy makers in formulating more effective poverty alleviation programs based on empirical evidence.